Case Report: Steroid-Responsive Takotsubo Cardiomyopathy Associated With Cytokine Storm and Obstructive Shock - Gudenkauf, Brent; Goetsch, Michael R.; Vakil, Rachit M.; Cingolani, Oscar; Adamo, Luigi (Frontiers in Cardiovascular Medicine, 2022)
A growing body of evidence suggests that inflammation may play a key role in the development of Takotsubo stress cardiomyopathy. Here we report the case of a 63-year-old woman who presented with chest pain and was diagnosed with this cardiomyopathy. After an initial improvement, the patient experienced a systemic inflammatory response of unclear origin and deteriorated rapidly into obstructive shock. Her presentation was considered consistent with cytokine storm. She was therefore treated with steroids with rapid improvement in her clinical picture. She relapsed after taper. Endomyocardial biopsy soon after initiation of pulse dose steroids showed macrophage and lymphocytic infiltration. This case highlights the potential intimate connection between systemic inflammatory response and Takotsubo stress cardiomyopathy and contributes to the evolving understanding of inflammation in the pathogenesis of this disease.